Investigation Of Polyvinyl Alcohol Added With Calcined Mussel Shell Biocomposite - Tiang, Ming Wai (2020)
This study is to investigate the characteristics of polyvinyl alcohol (PVOH) added with different amount of calcined mussel shell (HAp). HAp was extracted from the shell of Perna viridis through thermal calcination and followed by solution casting method to produce PVOH composite films, consisting 0 phr to 5 phr calcined mussel shell. The tensile strength of the PVOH composites increases upon added with 2 phr calcined mussel shell then decreases when amount of calcined mussel shell increases to 4 phr. For the Young’s modulus, it has similar trend as the tensile strength whereas addition of small amount of calcined mussel shell could provide the reinforcement effect while decreased in interfacial adhesion effect due to the agglomeration at high loading level of calcined mussel shell. The elongation at break of the PVOH composites was increased when the amount of calcined mussel shell added increased. For scanning electron microscopy, cavities can be observed in the PVOH composites with less amount of calcined mussel shell while flake like structure can be observed in PVOH composites with greater amount of calcined mussel shell. For X-ray diffraction analysis, the peak broadening effect indicates a decrease in HAp crystallite size which has ruptured and well dispersed within PVOH matrix. Addition of calcined mussel shell into PVOH matrix had weaken the water absorption capability of PVOH composites. In fourier transform infrared spectroscopy analysis, the significant peaks occurred approximately at 3254 cm-1 and 2940 cm-1 , indicating the presence of O-H group bonding and CH bonding respectively. Besides that, the strength of hydrogen bonding in the PVOH composites had increased as the amount of calcined mussel shell increased.